Volume 4: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Compressor Protection System on Rundown Characteristics

Abstract: Knowledge of compressor system behaviour during trip is essential to obtain reliable operation. Experience at Troll Kollsnes gas treatment plant has shown that the compressor can suffer from surge and rotating stall in situations with voltage drops in the electricity grid. The electric motor driven compressor and the protection valves and piping has been modelled and dynamic simulations has been done to reveal the transient response. An elaborate plant model has been created with the dynamic simulation tool OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A parametric study on a compressor station composed of five multistage centrifugal compressors in parallel was carried out in Refs. [42,43].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A parametric study on a compressor station composed of five multistage centrifugal compressors in parallel was carried out in Refs. [42,43].…”
Section: Introductionmentioning
confidence: 98%
“…Different models [10,[39][40][41][42][43][44] have been presented in literature dealing with modeling compression systems and set up of surge avoidance strategies. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A study of transients during emergency shutdown (ESD) showed the importance of the placement of the recycle valve and signal delay time to avoid surge during compressor run-down [5]. Other studies [6] and [7] have reported the experience from the analysis of compressors and driver behaviour during rundown for Troll Kollsnes gas treatment plant compressors. Morini [2] developed a one-dimensional dynamic compressor model based on first principles for simulation of transient behaviour.…”
Section: Introductionmentioning
confidence: 99%